(untitled) (Research, Society and Development, 2021)
Objective: To map and synthesize the scientific evidence of the performance of the community health worker based on the attributes of primary health care for leprosy control actions. Methodology: Scoping review, according to Joanna Briggs Institute and PRISMA-ScR. The research was carried out in electronic databases, in the Virtual Health Library, in the Cumulative Index to Nursing and Allied Health Literature (CINAHL), in the U.S National Library of Medicine, in the National Institutes of Health (PubMed), in the Gray Literature Report, and in the Google Scholar. Data collection took place on April 7, 2021, with the time limit established between 1991 and April 2021. Results: 359 scientific evidences were identified and after the application of the 4 stages of inclusion, resulted in 13 evidences. Most surveys were carried out in the southeastern region of Brazil between the years 2005 to 2019. The main evidence found was categorized according to the attribute. Gateway: Registration of cases, detection of signs and symptoms in the community, home visit to detect new cases, application of a questionnaire with questions about signs and symptoms. Continued care: Adherence to treatment, checking for unwanted reactions and supervision of the daily dose. Comprehensiveness: surveillance of household contacts. Family counseling: guidance on continuous treatment and home visits for guidance. Community orientation: group meetings, school sensitization and production of teaching material by the teaching and service team. Professional guidance: training. Final Considerations: The results emphasized the need for professional training and, on the other hand, the importance of their work with the individual, family, groups and society was highlighted.